2016
DOI: 10.7205/milmed-d-14-00740
|View full text |Cite
|
Sign up to set email alerts
|

Family Relational Health, Psychological Resources, and Health Behaviors: A Dyadic Study of Military Couples

Abstract: In addition to facing stressors that are typical of life course development (e.g., marital struggles, balancing work/family demands), military families face additional stress attributed to their military context (e.g., deployments, relocations). Using a systems framework and stress process perspective, this study examined military couples' relational health, as a gauge for how couples collectively cope and address challenges as a united front and how their relational health influences crucial health behaviors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…For instance, how do positive relationships with others improve individual or family well-being? Although multiple pathways can exist simultaneously, some research has suggested relationships are associated with enhanced well-being because positive relationships increase self-efficacy and self-worth and also increase the likelihood of engaging in health-promoting behaviors (Mancini, Bowen, O'Neal, & Arnold, 2015;O'Neal, Lucier-Greer, Mancini, Ferraro, & Ross, 2016;Umberson, Crosnoe, & Reczek, 2010). These processes can sometimes be pinpointed as a single moment or event, but often they are gradual, occurring slowly over time.…”
Section: Transitions and Change: Antecedents Processes And Resultsmentioning
confidence: 99%
“…For instance, how do positive relationships with others improve individual or family well-being? Although multiple pathways can exist simultaneously, some research has suggested relationships are associated with enhanced well-being because positive relationships increase self-efficacy and self-worth and also increase the likelihood of engaging in health-promoting behaviors (Mancini, Bowen, O'Neal, & Arnold, 2015;O'Neal, Lucier-Greer, Mancini, Ferraro, & Ross, 2016;Umberson, Crosnoe, & Reczek, 2010). These processes can sometimes be pinpointed as a single moment or event, but often they are gradual, occurring slowly over time.…”
Section: Transitions and Change: Antecedents Processes And Resultsmentioning
confidence: 99%
“…Increasingly within the family science literature, there have been discussions of the transactional effects (i.e., inter‐individual or “partner” effects) that exist within romantic relationships whereby one partner influences the other partner (e.g., O'Neal, Lucier‐Greer, Mancini, Ferraro & Ross, ). In our analyses, there are two instances where this is evident.…”
Section: Discussionmentioning
confidence: 99%
“…[2829] Poor perception of relations with spouse may contribute to development of mental health disorder through depleted psychological resources and unhealthy behavior in such individuals. [30]…”
Section: Discussionmentioning
confidence: 99%